What is the risk of esophageal adenocarcinoma in patients with Barrett's esophagus?. Issue 7 (July 2017) - Ganzer, Brandon; Powell, Charles
Abstract : EVIDENCE‐BASED ANSWER : The risk of esophageal adenocarcinoma (EAC) in patients with Barrett's esophagus (BE) is estimated to be 0.12% to 0.63% annually (SOR: A, meta‐analysis of longitudinal studies and 2 population‐based studies). Risk factors for progression to EAC include male sex, more than 3 cm of Barrett's mucosa, and dysplasia or metaplasia on index biopsy (SOR: B, 1 population‐based study).